2018
DOI: 10.1038/s41598-018-26104-1
|View full text |Cite
|
Sign up to set email alerts
|

Ancient acquisition of “alginate utilization loci” by human gut microbiota

Abstract: In bacteria from the phylum Bacteroidetes, the genes coding for enzymes involved in polysaccharide degradation are often colocalized and coregulated in so-called “polysaccharide utilization loci” (PULs). PULs dedicated to the degradation of marine polysaccharides (e.g. laminaran, ulvan, alginate and porphyran) have been characterized in marine bacteria. Interestingly, the gut microbiome of Japanese individuals acquired, by lateral transfer from marine bacteria, the genes involved in the breakdown of porphyran,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…1B) . Among strains that grew on alginate, all for which a sequenced genome was available contained known alginate utilization genes 6,7 and loci from representatives in each species were upregulated >100-fold in response to growth on alginate ( Extended Data 1 ). Growth on the remaining polysaccharides was even less prevalent, with only the single, previously known isolate of Bacteroides plebeius from a Japanese adult showing growth on porphyran and individual isolates belonging to two different species, B. thetaiotaomicron and B. ovatus , growing on carrageenan (a mixture of κ, λ isomers).…”
Section: Distribution Of Algal Polysaccharide Degradation In Human Gumentioning
confidence: 99%
See 1 more Smart Citation
“…1B) . Among strains that grew on alginate, all for which a sequenced genome was available contained known alginate utilization genes 6,7 and loci from representatives in each species were upregulated >100-fold in response to growth on alginate ( Extended Data 1 ). Growth on the remaining polysaccharides was even less prevalent, with only the single, previously known isolate of Bacteroides plebeius from a Japanese adult showing growth on porphyran and individual isolates belonging to two different species, B. thetaiotaomicron and B. ovatus , growing on carrageenan (a mixture of κ, λ isomers).…”
Section: Distribution Of Algal Polysaccharide Degradation In Human Gumentioning
confidence: 99%
“…As with nearly all dietary fibers, humans lack these enzymes and therefore rely on colonic bacteria for the ability to digest them. Previous studies have documented a few examples in which symbiotic bacteria belonging to Bacteroides— a dominant genus in humans—possess genes for degrading seaweed-derived porphyran 3,4 , agarose 5 , alginate 6,7 and laminarin 8 . In the first three cases, the genes involved often have closest homologs in marine Bacteroidetes, which are physiologically different from gut Bacteroides but share similar mechanisms for polysaccharide degradation 9 .…”
mentioning
confidence: 99%
“…Acquired genes allow the digestion of carbohydrates present in seaweeds that constitute an important fraction of the daily diet in this human population. Recently, Mathieu et al [32] have postulated the ancient acquisition of alginate (the main polysaccharide in the cell wall of brown algae) metabolism genes coming from marine Bacteroidetes by bacteria of the human gut microbiome. Despite in this case the acquisition is not restricted to Japanese people; authors suggest a similar scenario of acquisition via consumption of marine algae associated with occasional marine bacteria.…”
Section: Direct Impact Of Transfers Occurring In Human Microbiomesmentioning
confidence: 99%
“…Medicinal uses of seaweeds, as well as potential health benefits of consuming seaweeds, or seaweed-derived products have been extensively reviewed in the scientific literature and are indicative of their importance and growing applications, both in general (Fleurence and Levine 2016 ; Déléris et al 2016 ), as well as in specific cases, such as heart- and coronary diseases (Cornish et al 2015 ; Cardoso et al 2015 ; Murai et al 2019 ), brain and neural development and diseases (Cornish et al 2017 ; Guo et al 2019 ; Schepers et al 2020 ; Hannan et al 2020 ), irritable bowel syndrome and the human microbiome (Mathieu et al 2018 ; Cornish et al 2019 ), prevention and treatment of various cancers (Mamvar et al 2013 ; Jiang and Shi 2018 ), viral infections (Domínguez 2013 ; Mazalovska and Kouokam 2018 ), and parasite infections (Shafiq et al 2018 ), as well as diabetes and obesity (Sharifuddin et al 2015 ; Husni 2018 ; Attjioui et al 2020 ; Bermanoa et al 2020 ). Furthermore, various bioactive compounds of seaweed origin, such as secondary metabolites (Holdt and Kraan 2011 ; Kim 2012 ; Collins et al 2016 ; Rosa et al 2020 ), nutraceuticals (Domínguez 2013 ; Shannon and Abu-Ghannam 2019 ) and other functional ingredients (Peñalver et al 2020 ), have been suggested for judicious use as prophylactics and interventions in disease prevention.…”
Section: Seaweeds Human Health and Disease Preventionmentioning
confidence: 99%